Exploring the Link Between Spirituality and Anxiety in the Elderly: A Cross-sectional Study at Patrang Community Health Center - Yanuari, Karina Paramita; Rasni, Hanny; Kurdi, Fahruddin; Susanto, Tantut (Journal of Rural Community Nursing Practice, 2025)
Background: Elderly individuals often experience anxiety due to age-related changes. Spirituality has been identified as a potential coping mechanism to mitigate anxiety. Purpose: This study aims to analyze the relationship between spirituality and anxiety in the elderly in the Patrang Health Center area. Methods: The research using cross-sectional correlation analysis, sample consisted of 106 respondents selected through probability sampling, namely proportionate random sampling according to the inclusion and exclusion criteria. The instruments used in this study were the Daily Spiritual Experience Scale (DSES) and Geriatric Anxiety Inventory (GAI) questionnaires. Results: The data were analyzed using descriptive analysis, it is known that most the elderly in the Patrang Health Center area have a high level of spirituality (81.1%) and a mild level of anxiety (64.2%). Based on the Spearman-rho correlation test, p-value of 0.000 and an r= -0.405 were obtained, indicating that there is a relationship between spirituality and anxiety in the elderly in the Patrang Health Center area. Negative correlation namely the higher the level of spirituality in the elderly, the lower the possibility of the elderly experiencing anxiety. Conclusions: It can be concluded that spirituality plays an important role in overcoming anxiety in the elderly. Spiritual beliefs function as a coping mechanism to manage anxiety and good spiritual well-being can minimize symptoms of anxiety in the elderly.